TELAAH SEMIOTIS PENGGUNAAN METODE PEMBELAJARAN FIKIH DAN KOMEDI PADA CHANNEL YOUTUBE PEMUDA TERSESAT - Zaqiyah, Arina Iqomataz; Fatwa, Alyan; Prayogi, Arditya (IAIN KENDARI, 2024)
This article was written against the background of the fact that on a YouTube channel, there are various meanings that can be captured, including meanings related to learning methods and comedy. In this case, there are facts related to interesting fiqh lessons as conveyed by the Lost Youth channel. This channel gives a different impression when conveying Islamic religious learning. This channel then combines comedy and fiqh learning methods so that it becomes a special attraction for the general public. Thus, this article will review what learning methods are available on the Lost Youth channel, as well as what types of comedy are available on the Lost Youth channel. Writing this article uses a type of research with a semiotic and qualitative approach with the research object of the Lost Youth YouTube channel. The data collection technique used is by using documentation data collection techniques because the focus of the research is a document in the form of a video. From the results of the study, it was found that there is an illustration of the use of learning and comedy methods on the Lost Youth channel. In every video on this channel, several use different methods and the questions are always answered in a light, comedic way but still has weight by Habib Husein Ja'far Al-Hadar.. It is this different presentation that attracts viewers to study religion, especially subjects fiqh, because studying religion on this channel is not judged even though the questions the viewers ask are strange. This is because according to Habib Husein Ja'far Al-Hadar guidance can be found through small things.